2021
DOI: 10.1016/j.radcr.2021.07.082
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocarditis following Comirnaty vaccination in a healthy man with previous SARS-CoV-2 infection

Abstract: Myopericarditis following mRNA Covid-19 vaccination has recently been reported to health authorities in a lot of countries. They can occur in very rare cases after either the Moderna (mRNA-1273 - Spikevax) or Pfizer-BioNTech (BNT162b2 - Comirnaty) vaccination. Cases predominately occur in younger adult men within 14 days following the second dose. In this article, we present a 56-year-old man with no prior medical history, whit the exception of a mild Covid-19 infection 4 months earlier, who experienced an epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…In melanoma studies, microneedle applied transcutaneously showed a higher fold of IgG antibody and excess CD8 + T cell response to inhibit the melanoma. A preclinical study on H1N1 examined that DNA vaccine incorporated in liposomes can be delivered orally, resulting in higher IgG titer and activity of T cell response (Park et al 2021 ). A new concept arises in COVID-19 development through inhalation of DNA vaccine directly by using nebulizer or metered-dose inhaler.…”
Section: Nano-based Vaccines In the Development Of A Potential Covid-19 Vaccinementioning
confidence: 99%
See 4 more Smart Citations
“…In melanoma studies, microneedle applied transcutaneously showed a higher fold of IgG antibody and excess CD8 + T cell response to inhibit the melanoma. A preclinical study on H1N1 examined that DNA vaccine incorporated in liposomes can be delivered orally, resulting in higher IgG titer and activity of T cell response (Park et al 2021 ). A new concept arises in COVID-19 development through inhalation of DNA vaccine directly by using nebulizer or metered-dose inhaler.…”
Section: Nano-based Vaccines In the Development Of A Potential Covid-19 Vaccinementioning
confidence: 99%
“…Both the vaccines are composed of lipid nanoparticles that show an efficacy of ~ 95% (Khurana et al 2021 ). Lipid nanoparticles have various advantages that make them suitable as a vehicle to deliver mRNAs, such as the biocompatibility to human use, stability during the passage, efficient encapsulation of the informant, and increased cellular uptake in vivo (Khurana et al 2021 ; Park et al 2021 ). The 5′ and 3′ untranslated regions of mRNA sequences can be engineered systematically to the nanoparticle to ensure efficient delivery (Zeng et al 2020 ).…”
Section: Nano-based Vaccines In the Development Of A Potential Covid-19 Vaccinementioning
confidence: 99%
See 3 more Smart Citations